Exploring Quality Evaluation of Innovation and Entrepreneurship Education in Higher Institutions Using Deep Learning Approach and Fuzzy Fault Tree Analysis - Wang, Changlin; Zheng, Puyang; Zhang, Fengrui; Qian, Yufeng; Zhang, Yiyao; Zou, Yulin (Frontiers in Psychology, 2022)
The quality of Innovation and Entrepreneurship Education (IEE) in higher institutions is closely related to the degree to which the Undergraduate (UG) absorb relevant innovation and entrepreneurship knowledge and their entrepreneurial motivation. Thus, an effective Evaluation of Educational Quality (EEQ) is essential. In particular, Fault Tree Analysis (FTA), a common EEQ approach, has some disadvantages, such as fault data reliance and insufficient uncertainties handleability. Thereupon, this paper first puts forward a theoretical model based on Deep Learning (DL) method to analyze the factors of IEE quality; consequently, based on the traditional FTA, Fuzzy Fault Tree Analysis (FFTA) is proposed to evaluate the reliability of IEE classroom teaching for college teachers and students. Finally, based on the top event of entrepreneurial teaching failure, the hyper-ellipsoid model is implemented to restrict the interval probability of basic events and describe the deviation of uncertain events. Further, the model accuracy is verified by Questionnaire Survey (QS), based upon which the factors of IEE quality are analyzed. The results show that the designed QS has good reliability, validity, and fitness; the path coefficients of cooperative ability to critical thinking and innovative thinking are 0.9 and 0.66, respectively, indicating that students' cooperative ability plays a vital role in the classroom teaching. By calculation, the probability of “teaching failure” in entrepreneurial classroom teaching is [0.395,3, 0.462,5]. To sum up, the proposed method can effectively and quantitatively evaluate the quality of IEE in higher institutions, thus providing a certain basis for formulating relevant improvement strategies. The purpose is to provide important technical support for improving the IEE quality.